Gas-Phase Synthesis of Pyrazolo[3,4-b]pyridin-4-ones - Mackay, Martha; Nortcliffe, Andrew; McNab, Hamish; Hulme, Alison N. (Synthesis, 2015)
Flash vacuum pyrolysis (FVP) at 500–600 °C of 1-substituted pyrazolylaminomethylene derivatives of Meldrum’s acid provides 1-substituted pyrazolo[3,4-b]pyridin-4-ones in high yields. If the 1-substituent is a tert-butyl group, FVP at 750–850 °C causes elimination of 2-methyl-1-propene to give the parent pyrazolo[3,4-b]pyridin-4-one.
Keywords: gas-phase reactions; pericyclic reactions; heterocycles; Meldrum’s acid; medicinal chemistry